Heat transfer intensification in a horizontal tube utilizing hexagonal perforated tube inserts (Journal of Naval Architecture and Marine Engineering, 2024)
In response to the century-long demand for heat energy, efficient use, conservation, and recovery of heat have become critical issues. Heat exchanger manufacturing, with its substantial capital and operational costs, now necessitates an efficient and energy-saving approach. Various methods have been developed over the years to enhance heat transfer within these systems to improve performance and reduce fuel consumption. One such approach is passive heat transfer enhancement, which involves introducing geometric alterations in the flow medium, such as using inserts or modifying the tube surface. This study aims to examine flow and heat transfer behavior within a horizontal tube, employing hexagonal perforated tube (HPT) inserts with varying diameter ratios (DR). To achieve this, a 3D model of the HPT inserts was developed and analyzed using finite volume based ANSYS Fluent software. The investigation considered Reynolds numbers (Re) within laminar flow regions, ranging from 1118 to 1676 while exploring HPT inserts with DR of 0.167, 0.238, 0.357, and 0.476, respectively. Results reveal that the Nusselt number (Nu) is notably influenced by both Re and DR of the HPT inserts. The enhancement in Nu achieved through the use of HPT inserts can reach up to an impressive 60.4% compared to the plain pipe's performance, offering substantial benefits in terms of energy conservation and system performanceJournal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 155- 168